2001
DOI: 10.1006/jctb.2000.2013
|View full text |Cite
|
Sign up to set email alerts
|

The Extremal Function for Complete Minors

Abstract: Let c(t) be the minimum number c such that every graph G with e(G) c |G| contracts to a complete graph K t . We show that c(t)=(:+o(1)) t -log t

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
224
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 236 publications
(232 citation statements)
references
References 19 publications
6
224
0
2
Order By: Relevance
“…Average degree Ω(t √ log t) forces K t as a minor (Kostochka [12], Thomason [20]), and this bound is best possible. For subdivisions, an old conjecture of Mader and Erdős-Hajnal, which was eventually proved by Bollobás and Thomason [3] and independently by Komlós and Szemerédi [11], says that there is a constant c such that every graph with average degree at least ct 2 contains a subdivision of K t , and this is tight apart from the constant c. The corresponding extremal problem for complete graph immersions has been proposed in [6].…”
Section: Conjecture 11mentioning
confidence: 99%
“…Average degree Ω(t √ log t) forces K t as a minor (Kostochka [12], Thomason [20]), and this bound is best possible. For subdivisions, an old conjecture of Mader and Erdős-Hajnal, which was eventually proved by Bollobás and Thomason [3] and independently by Komlós and Szemerédi [11], says that there is a constant c such that every graph with average degree at least ct 2 contains a subdivision of K t , and this is tight apart from the constant c. The corresponding extremal problem for complete graph immersions has been proposed in [6].…”
Section: Conjecture 11mentioning
confidence: 99%
“…Thomason [41] showed that if the average degree of a graph is at least cp √ log p, then the graph contains K p as a minor (and that this bound is tight). His proof is very complicated and it is not clear if it can be turned into a polynomial-time algorithm to actually find such a minor.…”
Section: Finding Complete Topological Minorsmentioning
confidence: 99%
“…Assume that A is no larger than B, that is, A has at most p/2 vertices. By the result in [18], for sufficiently large d, G(A) has a subgraph H which can be contracted into a complete graph with m vertices where m > (3d/8) 1− . That is, H contains m pairwise disjoint connected subgraphs such that any two of these connected subgraphs are joined by at least one edge.…”
Section: The Smallest Number Of Cycles In 3-connected Graphsmentioning
confidence: 99%